Effect of Group Contingency Type on Walking: Comparisons of Effectiveness and Cost Efficiency - Kim, Heewon; Lee, Changseok; Lee, Seoi; Chung, Kyong-Mee (Frontiers in Psychology, 2021)
This study examined the effect of technology-based group contingency on walking among adults and compared the effectiveness and cost-efficiency between three types of contingency. Seventy-two students were divided into teams of three. Each team was randomly assigned to one of three group contingency conditions (independent, interdependent, or dependent), undergoing 66 days of technology-based group contingency intervention. Sixty-five participants completed the intervention and 61 completed the follow-up assessment two months later. Step counts and self-reported walking activity increased after the intervention under all three conditions. The proportion of participants meeting the target step counts was significantly higher under the dependent group contingency condition. However, intervention effects were not maintained two months later under any condition. For cost-efficiency, increases in step count per point were significantly greater under the interdependent group contingency condition. Group cohesion and social validity (point satisfaction and point utility) were significantly higher under the dependent group contingency condition. Finally, the clinical implications and limitations of this study are discussed.